2017
DOI: 10.1016/j.paid.2017.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and depressive symptoms: The effects of psychological detachment from work

Abstract: We examined the association of perfectionism with depressive symptoms and tested whether psychological detachment from work would both mediate and moderate the association. The participants were 76 primary school teachers (87% female) who responded to measures of perfectionism (Multidimensional Inventory on Perfectionism in Sports adapted for teachers), psychological detachment from work (The Recovery Experience Questionnaire), and depressive symptoms (Beck Depression Inventory-II). Perfectionism comprised bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…One set of key findings regarding the influence of perfectionism on job attitudes is that perfectionistic concerns are more strongly related to negative job attitudes such as dissatisfaction (Fairlie & Flett, ; Hochwarter & Byrne, ; Mitchelson & Burns, ; Price, ), psychological detachment from work (Gluschkoff et al, ), and reduced commitment (Bousman, ) than are perfectionistic strivings. These effects appear to be because individuals with high levels of perfectionistic concerns are unable to derive a real sense of accomplishment, which may heighten negative reactivity to tasks and events (Dunkley, Mandel, & Ma, ; Hewitt & Flett, ).…”
Section: Review Of Perfectionism In the Workplacementioning
confidence: 99%
See 2 more Smart Citations
“…One set of key findings regarding the influence of perfectionism on job attitudes is that perfectionistic concerns are more strongly related to negative job attitudes such as dissatisfaction (Fairlie & Flett, ; Hochwarter & Byrne, ; Mitchelson & Burns, ; Price, ), psychological detachment from work (Gluschkoff et al, ), and reduced commitment (Bousman, ) than are perfectionistic strivings. These effects appear to be because individuals with high levels of perfectionistic concerns are unable to derive a real sense of accomplishment, which may heighten negative reactivity to tasks and events (Dunkley, Mandel, & Ma, ; Hewitt & Flett, ).…”
Section: Review Of Perfectionism In the Workplacementioning
confidence: 99%
“…On the other hand, we note that some researchers (e.g., Caliskan, Arikan, & Saatchi, ; Corrigan, ; Fairlie, ) found the opposite effects, reporting that perfectionistic strivings positively correlate with exhaustion and cynicism. In addition, self‐oriented perfectionism has also yielded positive associations with performance anxiety (Kobori, Yoshie, Kudo, & Ohtsuki, ; Mor, Day, Flett, & Hewitt, ), stress (Matlon, ), low self‐esteem (Ogus, ), and depressive symptoms (Gluschkoff et al, ).…”
Section: Review Of Perfectionism In the Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…In general, prior empirical investigations have demonstrated perfectionistic strivings as a positive and perfectionistic concerns as a negative form of perfectionism (Stoeber, 2018). Perfectionistic concerns have been strongly related to negative job attitudes such as dissatisfaction, burnout, reduced commitment, and detachment from work (Bousman, 2007; Fairlie & Flett, 2003; Gluschkoff et al, 2017). Perfectionistic strivings have been linked to desirable outcomes such as research productivity, innovative behavior, efficacy, and lower burnout (Chang, Chou, Liou, & Tu, 2016; Childs & Stoeber, 2010; Sherry, Hewitt, Sherry, Flett, & Graham, 2010).…”
Section: Perfectionismmentioning
confidence: 99%
“…However, perfectionistic strivings have not always been linked to positive outcomes, as some studies have reported the opposite pattern such as association with heightened burnout, anxiety, and depressive symptoms, (Childs & Stoeber, 2010; Kobori, Yoshie, Kudo, & Ohtsuki, 2011; Li, Hou, Chi, Liu, & Hager, 2014). In sum, some researchers argue that perfectionistic strivings are a beneficial and healthy form of perfectionism (Stoeber & Otto, 2006), but not all researchers agree (Flett & Hewitt, 2006; Gluschkoff et al, 2017). The notion that perfectionism includes positive and negative dimensions continues to be a source of debate among perfectionism researchers (Ocampo et al, 2019).…”
Section: Perfectionismmentioning
confidence: 99%